Plasmonic-tape-attached multilayered MoS2 film for near-infrared photodetection - Park, Minji; Kang, Gumin; Ko, Hyungduk (NATURE PUBLISHING GROUP, 2020)
Molybdenum disulfide has been intensively studied as a promising material for photodetector applications because of its excellent electrical and optical properties. We report a multilayer MoS2 film attached with a plasmonic tape for near-infrared (NIR) detection. MoS2 flakes are chemically exfoliated and transferred onto a polymer substrate, and silver nanoparticles (AgNPs) dewetted thermally on a substrate are transferred onto a Scotch tape. The Scotch tape with AgNPs is attached directly and simply onto the MoS2 flakes. Consequently, the NIR photoresponse of the MoS2 device is critically enhanced. The proposed tape transfer method enables the formation of plasmonic structures on arbitrary substrates, such as a polymer substrate, without requiring a high-temperature process. The performance of AgNPs-MoS2 photodetectors is approximately four times higher than that of bare MoS2 devices.
Keywords: BROAD-BAND